Development and implementation of a dynamic and 4D GIS based on semantic location model. Issue 3 (3rd July 2019) - Zhu, Xinyan; Hu, Tao; Ye, Xinyue; Guo, Wei; Huang, Liang; Xiong, Hanjiang; Ai, Haojun; She, Bing; Xiong, Qing; Duan, Lian
ABSTRACT: In the big data era, robust solutions are obliged to be proposed to integrate and represent data from different formats and with different contents to assist the decision-making. Current cartographic and geographic information systems have limited capabilities for solving these problems. This paper describes an automatic and comprehensive system that conducts data fusion from all potentially related sources. In this system, a new Semantic Location Model (SemLM) is established to present the semantic concepts and location feature and demonstrate how locations are interrelated. In the SemLM, various types of location descriptors in different application scenarios can be analyzed and understood. Additionally, considering the challenges involved in data-intensive computation and visualization, this paper implements a Place-based Pan-Information System (P2S) as an innovative 4D system that dynamically associates and visualizes place-based information, using public security as the case study.